Church and Capitalism - Torre, Comte (Relations industrielles / Industrial Relations, 1949)
There have been many quotations made these days from an article of the Church and capitalism which appeared in the « Osservatore Romano » under the signature of its director, the Count della Torre. We are giving here some extracts.